Team incentives and leadership - Drouvelis, Michalis; Nosenzo, Daniele; Sefton, Martin (Elsevier, 2017)
We study, experimentally, how two alternative incentive mechanisms affect team performance and how a team chooses between alternative mechanisms. We study a group incentive mechanism (team output is shared equally among team members) and a hierarchical mechanism (team output is allocated by a team leader). We find that output is higher when a leader has the power to allocate output, but this mechanism also generates large differences between earnings of leaders and other team members. When team members can choose how much of team output is to be shared equally and how much is to be allocated by a leader they tend to restrict the leader’s power to distributing less than half of the pie.